Italiano con l'immaginario Tre canovacci di simulation globale - Montali, Sandra (bu,press, 2016)
Italiano con l'immaginario introduces a humanistic approach of language teaching little known in Italy, deriving from the French teaching tradition. Simulation globale is a language teaching course which, instead of offering many detached activities and using a standard manual, follows a path on which all elements are connected by a narrative thread. Thus, the oral and written production of a large number of texts takes place within a very motivating context.